Pengaruh Pemanfaatan Sistem Informasi Akuntansi dan Kinerja Sosial terhadap Pengungkapan Keberlanjutan pada Perusahaan ESG Quality 45 - Yudan Hartawan; Acep Komara; Mada Purwanto W. N (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This research is motivated by the persistently low quality of corporate sustainability disclosure in Indonesia, despite the growing global trend of non-financial reporting. Drawing on the Legitimacy Theory framework, this study aims to analyze the influence of Accounting Information System utilization and corporate social performance on the level of sustainability disclosure. The study employed a quantitative approach using multiple linear regression on companies included in the IDX KEHATI ESG Quality 45 index for the 2021–2024 period. The sample was selected using purposive sampling to obtain representative data. The analysis shows that both Accounting Information Systems and social performance have a positive and significant impact on sustainability disclosure, with social performance being the most dominant variable in driving corporate information transparency. These findings indicate that optimizing technology-based information systems and a demonstrated commitment to social responsibility can enhance the quality of sustainability reporting, making it more credible and accountable. Therefore, integrating accounting technology and strengthening social performance are fundamental strategies for encouraging more sustainable reporting practices in public companies in Indonesia to meet stakeholder expectations.